A STUDY OF REDUCING ENERGY CONSUMPTION IN THE CHILLER-TYPE AIR CONDITIONING SYSTEM BY INCREASING THE SYSTEM EFFICIENCY AND DECREASING THE THERMAL LOAD - IRSYAD (NIM : 33112002), MUHAMMAD
The increasing needs of energy have to be consistent with its usage efficiency. Air conditioning (AC) system needs more efficiency as it is one of the largest consumers of energy in the commercial building sector. The strategy to reduce the energy consumption is employed by gaining a higher air conditioning performance and compressing the building cooling load. One of the strategies being developed for the study is by employing phase change material (PCM) as materials in the secondary refrigerant to accelerate its thermal capacity. Another strategy is experimented by minimizing the solar heat energy which radiated through the walls and roofs. The green roof installation and the PCM application for the walls absorb the thermal energy entering through the wall. To support the downscaling of energy consumption for the chiller, the study of phase-change materials and the green roof is required. This dissertation examines some affordable natural PCMs and salt-hydrates from Indonesian’s resources. This research is aimed at reducing the energy consumption of the chiller type AC system by employing alternative PCM as the material for the secondary refrigerant and reducing of thermal load by green roof and PCM in the wall. To achieve the purpose of the study, this dissertation is divided into two parts; the study of PCM as the material for the secondary refrigerant, and the study of the room thermal energy downsizing. To generate the appropriate alternative PCM, this study examines the material characteristics, the heat transfer and flow characteristics, and the application of the chiller-AC system. To assess the room thermal load decrease, this study performs the experiment to assess the heat transfer through the green roof and the PCM-added walls. To analyze the effect of the PCM and the green roof application for the commercial buildings, this study calculates the thermal load and the AC system energy consumption after the experiments have been accomplished. The study indicates that CaCl2•9H2O, Na2HPO4•149H2O, and Nyamplung oil are the best PCM candidates based on their thermal characteristics. Each material has a high latent heat value as much as 315,37 kJ/kg, 215,94 kJ/kg dan 184,47 kJ/kg. Other characteristics of the PCM are their density and viscosity which are demonstrated in the resulted empirical equation.The limitation of these PCMs is the rising degree of the pressure drops inside the piping system. The arise becomes significant as the fluids phase change momentum forms the solid particles. Therefore, the application of Tween 80 200 ppm surfactant gives a benefit in decreasing 20% of the average pressure drop for Na2HPO4•149H2O. The excellence of the selected PCM is on their increased heat transfer flow rate; CaCl2•9H2O has 18,62% increase, Na2HPO4•149H2O has 13,9% increase, while Nyamplung oil has no significant increased percentage. The PCMs’ heat transfer formulate a new Nusselt equation. CaCl2•9H2O salt hydrate and Na2HPO4•149H2O salt hydrate are prospective potential secondary refrigerants developed in the future based on the experiment on the application. They minimize the total energy consumption in the pump and the compressor as much as 7,5%, and 3,43%, along with the result indicated in the equation for 50-storey commercial building that recognizes the ability of the salt hydrates to downscale the chiller energy consumption as much as 4,3% in the CaCl2•9H2O, 2,5% in the Na2HPO4•149H2O, dan 5,4% in the Na2HPO4•149H2O + Tween 80 200 ppm. The room thermal load are reduced up to 2,7% by extending the PCM panel using the coconut oil. In addition, the application of the green roof compresses the floor thermal load as much as 20%. Thus, the integrated application of the green roof and the PCM paneled wall downscales the building thermal load as much as 3,3%. The material's phase change performed in the panel lowers the thermal energy as much as 6,4% on the daylight.